2011
DOI: 10.1007/s00167-011-1473-5
|View full text |Cite
|
Sign up to set email alerts
|

Hop tests correlate with IKDC and KOOS at minimum of 2 years after primary ACL reconstruction

Abstract: Purpose The hypothesis of this study was that single-legged horizontal hop test ratios would correlate with IKDC, KOOS, and Marx activity level scores in patients 2 years after primary ACL reconstruction. Methods Individual patient-reported outcome tools and hop test ratios on 69 ACL reconstructed patients were compared using correlations and multivariable modeling. Correlations between specific questions on the IKDC and KOOS concerning the ability to jump and hop ratios were also performed. Results The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 28 publications
1
93
0
Order By: Relevance
“…Reductions in quadriceps strength and greater limb asymmetry after ACLR have been associated with altered landing mechanics, 19,33 reductions in functional performance, 19,22 and decreased patient-reported knee-related function. 34 Without optimal and symmetrical quadriceps function, individuals may have difficulty adapting to the demands of daily function and recreational activity after ACLR due to a decreased ability to absorb knee-joint loads during weight bearing. In this study, participants with ACLR had returned to a level of physical activity similar to that of their healthy counterparts; however, they continued to report reduced knee-related function as measured by the International Knee Documentation Committee form.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in quadriceps strength and greater limb asymmetry after ACLR have been associated with altered landing mechanics, 19,33 reductions in functional performance, 19,22 and decreased patient-reported knee-related function. 34 Without optimal and symmetrical quadriceps function, individuals may have difficulty adapting to the demands of daily function and recreational activity after ACLR due to a decreased ability to absorb knee-joint loads during weight bearing. In this study, participants with ACLR had returned to a level of physical activity similar to that of their healthy counterparts; however, they continued to report reduced knee-related function as measured by the International Knee Documentation Committee form.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that lower extremity functional performance test results predict future functional outcome, 1,8,12,21,22 indicating their usefulness in lower extremity rehabilitation.…”
Section: 19mentioning
confidence: 99%
“…Consequently, these tests can reveal impairments in muscle force generation or proprioception and neuromuscular control that might not be obvious with other clinical measures. 7,19 Several studies have found that lower extremity functional performance test results predict future functional outcome, 1,8,12,21,22 indicating their usefulness in lower extremity rehabilitation.…”
mentioning
confidence: 99%
“…Functional tests are intuitively appealing due to their close resemblance to actual athletic motions, and they have been correlated to self-reported outcome measures [16]. However, none of the functional tests, nor any other post-operative tests, have been directly correlated to successful return to play or decreased re-injury rates.…”
Section: Original Studymentioning
confidence: 99%
“…Previous research has established the reliability of this testing battery [5][6][7][8][9]. Performance on these tests is correlated to self-reported ability in the post-op period, although no research has directly linked it to lower re-injury rates or successful return to play [10].…”
Section: Introductionmentioning
confidence: 99%